Autogenous regulation of the synthesis of glutamine synthetase in Klebsiella aerogenes. - Bender, R A (1977)
We isolated an F' episome of Escherichia coli carrying the glnA+ gene from K. aerogenes and an F' episome of E. coli carrying the glnA4 allele from K. aerogenes responsible for the constitutive synthesis of glutamine synthetase. Complementation tests with these episomes showed that the glnA4 mutation (leading to the constitutive synthesis of active glutamine synthetase) was in the gene identified by mutations glnA20, glnA51, and glnA5 as the structural gene for glutamine synthetase. By using these merodiploid strains we were able to show that the glnA51 mutation lead to the synthesis of a glutamine synthetase that lacked enzymatic activity but fully retained its regulatory properties. Finally, we discuss a model that explains the several phenotypes associated with mutations such as glnA4 located within the structural gene for glutamine synthetase leading to constitutive synthesis of active glutamine synthetase.